Centers and limit cycles of vector fields defined on invariant spheres - Buzzi, Claudio A (2021)
This version of the article has been accepted for publication, after peer review (when applicable) but is not the Version of Record and does not reflect post-acceptance improvements, or any corrections. The Version of Record is available online at: http://dx.doi.org/10.1007/s00332-021-09751-z.